Method for selecting strategy of communication of multiple simulators in an environment based on the HLA standard - Krzysztof PANUFNIK; Tadeusz NOWICKI (Communications of International Proceedings, 2025)
The paper presents a new method of selecting communication strategy for simulators connected in the HLA architecture (high-level architecture). The HLA architecture is fundamental for communication between different simulators. It is the modern standard for communication in this area. Simulators connected in this architecture, called federates, often use common data, the values of which can change. Information about changes is sent to other federates interested in these changes. Communication usually places a heavy burden on the network with federates. It turns out that depending on the method of sending messages between federates, the load on the entire system can vary greatly. The motivation for this work was to develop a strategy for broadcasting information about changes that cause the lowest communication load in the network. There are various strategies for transferring data in HLA reported in literature. Unfortunately, there are only a few adequately effective methods to solve this problem. Moreover, they are not efficient enough. The paper presents a new method to solve that problem. The motivation for this work was therefore to develop a new, more efficient, information broadcasting strategy that causes the lowest communication load in the network. Comparative studies in a simulation environment have shown that the new method is more effective than those previously proposed.
Keywords: simulation; standard HLA; data distribution service; data communication management